The breach - Lee, Patrick (New York : Harper, 2010)
"Trying to regain his life in the Alaskan wilds, ex-con/ex -cop Travis Chase stumbles upon an impossible scene: a crashed 747 passenger jet filled with the murdered dead, including the wife of the President of the United States. Though a nightmare of monumental proportions, it pales before the terror to come, as Chase is dragged into a battle for the future that revolves around an amazing artifact. Allied with a beautiful covert operative whose life he saved, Chase must now play the role he's been destined for--a pawn of incomprehensible forces or humankind's final hope--as the race toward Apocalypse begins in earnest."--p. [4] of cover.
Keywords: End of the world -- Fiction; Intelligence officers -- Fiction; Supernatural -- Fiction; Suspense fiction